Peran Penyuluh Agama Honorer dalam Meningkatkan Kegiatan Keagamaan di Masyarakat Desa Batu Dewa Kecamatan Curup Utara Kabupaten Rejang Lebong - Din, Cik (Sekolah tinggi Agama Islam Negeri (STAIN) Curup, 2016)
This study discussed on the effectiveness of the role and function of religious concelor in the society of Batu Dewa. It is considered by the lack of religious activities accompanied with the development of non-Muslim community. Then the synchronization between duty and registration of religious honorary counselor on the conditions of diversity and the society religious activities in the office of Religious Affairs District of Curup Utara. This research was a qualitative. The data collection was done by conducting observation, interviews and documentation. Data analysis was done by reviewing all data starting from data collection, data reduction, data display, and conclusion or verification. The results showed that the role of religious honorary concelor in improving religious activities in the community of Batu Dewa were: as a facilitator, mediator and motivator in implementing the guidance of reading and writing the Quran, taking part in Islamic commemorating activities, and deliver islamic speech in the society. There were two Factors determined the changes of the worship behavior of children in the Batu Dewa of Curup Utara District, namely: internal factors interms of: motivation, talent, and needs. Then external factors in the forms of social, cultural, physical environment and spiritual environment.